IMMU-20. IMMUNE AND TUMOR BIOMARKERS OF OUTCOME IN REPLICATION REPAIR DEFICIENT BRAIN TUMORS TREATED WITH IMMUNE CHECKPOINT INHIBITORS: UPDATES FROM THE INTERNATIONAL REPLICATION REPAIR DEFICIENCY CONSORTIUM. (23rd April 2019) - Bouffet, Eric; Sudhaman, Sumedha; Chung, Jiil; Campbell, Brittany; Kelly, Jacalyn; Coblentz, Ailish; Edwards, Melissa; Lipman, Tatiana; Zhang, Cindy; Ercan, Ayse Bahar; Sambira, Lauren; Bendel, Anne; et al.
Abstract: Pediatric brain tumors with replication repair deficiency (RRD) are hypermutant and may respond favorably to immune checkpoint inhibition (ICI). We are collecting ongoing clinical and molecular data from patients with RRD hypermutant cancers treated with ICI as a part of our consortium registry study. Companion biomarkers include tumor mutational burden (TMB), neoantigens and genetic signatures obtained from whole genome and exome sequencing. Immune inference is obtained from RNAseq. Additionally, T-cell receptor rearrangement data are collected from the tumor and blood throughout treatment. From 2015–2018, 53 patients were treated with ICI and combination therapies. Of these 39 had brain tumors, with 93% having high grade gliomas. Two-year overall survival for the entire cohort is 47+/-8%, which compares favorably with historical controls. Tumor location had major impact on outcome. Non-CNS solid tumor patients have 2-year OS of 78+/-11%, all failures occurring within the first 2 months, and sustained responses are observed for 3 years. In contrast, OS for brain tumors is 39+/-10% with late recurrences observed even after 2 years of therapy (p=0.02). Large tumor size and total tumor burden are associated with higher rates of "flare" and poor outcome throughout all cancers. While all tumors are hypermutant, TMB and predicted neoantigens do not correlate with response. However, specific signatures extracted from SNVs and indels are significantly associated with response to ICI and favorable outcome (p=0.005). Notably, RRD IDH1 mutant glioblastomas have particularly poor response to ICI. Interestingly, glioblastomas (n=8) which failed single agent ICI had favorable responses to combination immunotherapies with prolonged survival of 65%+/-8% one year after failure vs 0 for untreated patients (p=0.01). The favorable outcome and responses to ICI are encouraging. Since brain tumors respond less favorably to ICI than other solid tumors, combination therapies based on tumor and immune signatures of these cancers may be beneficial.